CHILD CARE OR CHILD SCARE: ENHANCING THE LEGAL REQUIREMENTS ON HEALTH AND SAFETY IN CHILD CARE CENTRES LAWS AND REGULATIONS IN MALAYSIA - Mashitah Abdul Mutalib; Nik Salida Suhaila Nik Saleh; Nurfadhilah Mohamad Ali (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Health and safety are the required legal requirements that need to be regulated in-laws and regulations of child care centres. These legal requirements are categorised as structural quality features which are often translated into laws and regulations in ensuring quality child care for children. This paper examines the question of whether the health and safety legal requirements necessitate improvements in the legislative framework of Malaysian child care. The laws and regulations in Malaysia on health and safety requirements as stated in the Child Care Centre Act 1984 and Child Care Centre Regulation 2012 are evaluated according to the relevant sections and regulations. Recommendations are made in enhancing laws and regulations in child care centres in Malaysia regarding health and safety. The qualitative method was used in this study using document analysis especially the related laws in Malaysia. Cross-reference to other jurisdictions’ laws and regulations such as Australia and Singapore was also conducted. In conclusion, enhancement on health and safety features need to be made especially with regards to knowledge on child protection law amongst child care providers, prohibition of employment, laws, and regulations on incidents, injury and trauma, and medicine and drugs administration.